TEACHING ENGLISH LITERACY TO CHILDREN - Ariatna Ariatna (BAHAS, 2015)
The topic of literacy is of special interest among language scholars and educators. Again and again the discussion returns to the question of how to best teach literacy. Despite the controversy over the methods of teaching literacy, the contemporary literature on literacy repeatedly describes teachers as having the power to make a change. This paper discusses what teachers need to know about teaching literacy and how to do the teaching to children. Key Words: Literacy, Teacher, Written Language, Oral Language